51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-491
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Performance Function for the Control of Flow Separation

Abstract: Feedback control of aerodynamic flow separation is a formidable challenge due to the nonlinear system dynamics and the lack of a closed-form model that describes these dynamics. Recently, adaptive control approaches have been employed to meet this challenge. However, the performance and robustness achieved using these algorithms is limited due to the fact that the sensors in flow control systems are not used to estimate lift and drag, the quantities of interest. This paper derives a physics-based performance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…18, 19, and 20 of Appendix A. These and more detailed data are presented in Reese et al 39 For the angles of attack and Reynolds numbers considered, Z lif t does increase and decrease in agreement with actual lift in both simulated and experimental data. .…”
Section: Experiments and Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…18, 19, and 20 of Appendix A. These and more detailed data are presented in Reese et al 39 For the angles of attack and Reynolds numbers considered, Z lif t does increase and decrease in agreement with actual lift in both simulated and experimental data. .…”
Section: Experiments and Resultsmentioning
confidence: 81%
“…The input for these tests was the solenoid valve voltage frequency, and the output was Z lif t , the lift based performance function computed from the transducer measurements at locations P1 through P4. This performance function, with a detailed derivation provided in Reese et al 39 with sensors located as indicated in Table 1, Z lif t may be computed as…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation